Current Therapeutic Approaches for Multidrug-Resistant and Extensively Drug-Resistant Acinetobacter baumannii Infections - Petros Rafailidis; Periklis Panagopoulos; Christos Koutserimpas; George Samonis (MDPI AG, 2024)
The treatment of Acinetobacter baumannii infections remains a challenge for physicians worldwide in the 21st century. The bacterium possesses a multitude of mechanisms to escape the human immune system. The consequences of A. baumannii infections on morbidity and mortality, as well on financial resources, remain dire. Furthermore, A. baumannii superinfections have also occurred during the COVID-19 pandemic. While prevention is important, the antibiotic armamentarium remains the most essential factor for the treatment of these infections. The main problem is the notorious resistance profile (including resistance to carbapenems and colistin) that this bacterium exhibits. While newer beta lactam/beta-lactamase inhibitors have entered clinical practice, with excellent results against various infections due to Enterobacteriaceae, their contribution against A. baumannii infections is almost absent. Hence, we have to resort to at least one of the following, sulbactam, polymyxins E or B, tigecycline or aminoglycosides, against multidrug-resistant (MDR) and extensively drug-resistant (XDR) A. baumannii infections. Furthermore, the notable addition of cefiderocol in the fight against A. baumannii infections represents a useful addition. We present herein the existing information from the last decade regarding therapeutic advances against MDR/XDR A. baumannii infections.